Fase Ketiga Teori Manajemen Keuangan: Neurofinance Sebagai Sebuah Pendekatan Baru - Kelen, Lusianus (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
This article aims to describe the development of financial management disciplines from 1844 to the present and discuss neurofinance as a new concept in overcoming some of the weaknesses of previous views or theories (traditional and behavioral views). This article also contains an overview of neurofinance as a new approach to behavior-based finance as well as a cross-disciplinary approach between finance, psychology, and neuroscience. In this study, the authors show that currently financial management theory is in its third phase, where the first phase is traditional financial, and the second phase is behavior finance. A literature study is used to explain the purpose of writing by collecting various literature sources and then conducting a review and analysis.